Theoretical and cultural perspectives on organizational justice - Gilliland, Stephen; Steiner, Dirk; Skarlicki, Daniel (Research in social issues in management., 2001)
At the 1998 annual conference of the Society for Industrial and Organizational Psychology, we organized a roundtable discussion session titled "Innovating organizational justice: Cultural, value, and stakeholders' perspectives." We were impressed by the high level of discussion that this session generated and decided to try to continue the discussion in a conference devoted to these issues. In the summer of 1999, approximately 20 scholars from seven nations met for two days in Nice, France. The theme of the "International Roundtable" on organizational justice was "Innovating research on organizational justice." The format of the meeting allowed for extensive discussion of each of the papers that were presented.A strong feeling that emerged from this meeting was that organizational justice research has much to contribute to our understanding of people at work. Further, our current research on organizational justice and the application of justice to managerial issues has in some ways been limited by the confines of our academic journals. The papers presented and discussed at the Nice roundtable clearly extended scholarly thinking in new and exciting directions. We invited a subset of the authors who presented their research at this meeting to submit their papers for review for the first volume of our newly developed series Research in Social Issues in Management. All papers were reviewed independently by organizational justice scholars.